Empowerment of Small Businesses through The Implementation of Qardhul Hasan Financing - Masyhuri Machfudz; Nahdhiatun Kamila (Publisher of Widyagama University of Malang (UWG Press), 2019)
The research aims to describe Qardhul Hasan financing and recognize the problems faced in micro businesses in the city of Malang. The study was conducted on two research objects. The first study was on a used motorcycle dealer business that received Qardhul Hasan during the 2016-2018 period. The second study in 2019, was the implementation of Qardhul Hasan in small-scale creative economy traders, whose source of funding came from 2.5 percent of profits from used motorcycle dealers. The results showed that the implementation of Qardhul Hasan financing was quite profitable. Qardhul Hasan who is allocated to the creative economy group indicates a feeling of happiness and calm because loan repayments are not burdened with costs, besides having flexibility from the time of repayment. Economic actors managed to collect savings from repaying loan installments. Qardhul Hasan funding received a reasonably good response from economic actors. Qardhul Hasan loan recipients should be able to maintain trust and uphold the agreements that have been built. This study has implications for the development of Qardhul Hasan, namely strengthening the concept of Qardhul Hasan as loan financing, and strengthening groups for small businesses to run the Qardhul Hasan management mechanism JEL Classification: D14, Q21, G51